The end of the novel of love - Gornick, Vivian 1935- (Beacon Press, 1997)
In this book of new and collected critical essays, Vivian Gornick turns the searching intelligence and honesty of insight that mark her memoirs on the work - and the lives - of writers she admires, among them Jean Rhys, Willa Cather, Christina Stead, and George Meredith. In doing so, she examines a century of novels of love-in-the-Western-world and comes to see that, for most writers, it is the drama of our angry and frightened selves in the presence of love that is our modern preoccupation.
Keywords: Amerikaans; Engels; Liefdesverhalen; Englisch; Closure (Rhetoric); Love stories, American -- History and criticism; Love stories, English -- History and criticism; Women and literature -- English-speaking countries; Women in literature; Literatur; Frau; Frau -- Motiv; Liebesgeschichte; USA; Aufsatzsammlung